Handbook of hybrid systems control : theory, tools, applications - Lunze, Jan; Lamnabhi-Lagarrigue, F. (Francoise), 1953- (Cambridge, UK ; New York : Cambridge University Press, 2009)
Includes bibliographical references and index.